Evaluation of alfalfa resistance to the pea aphid, Acyrtosiphon pisum [Homoptera : Aphididae] – Methodological aspects to improve a standardized speedling test - Girousse, C.; Bournoville, R.; Badenhausser, I. (Phytoprotection, 1998)
This study proposes a guide for the design of experiments to test alfalfa (Medicago sativa) for resistance to pea aphid infestation (Acyrthosiphon pisum). This test was conducted in controlled conditions on alfalfa seedlings. For the infestation, aphid population maintained on alfalfa was found to be more efficient than an aphid population reared on broad bean. When comparing alfalfa cultivars, a non-choice test gave the same results as a choice test, that was more difficult to perform. When infesting a unit of 54 seedlings at the cotyledon stage on the 1st and 5th day of the experiment, 360 mg compared with 180 mg and 540 mg aphids, led to the best compromise between levels of infestation and aphid stock culture availability. Infestation was stopped when more than 60% of susceptible cultivar seedlings were wilted or dead. Under these conditions, we calculated the number of replicates necessary to obtain a fixed level of difference. Six units per cultivar would distinguish between cultivars differing from 20% in their seedling mortality.